2014
DOI: 10.5709/acp-0154-5
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions, impulsivity, and inhibitory control in adolescents: A structural equation model

Abstract: Background. Adolescence represents a critical period for brain development, addressed by neurodevelopmental models to frontal, subcortical-limbic, and striatal activation, a pattern associated with rise of impulsivity and deficits in inhibitory control. The present study aimed at studying the association between self-report measures of impulsivity and inhibitory control with executive function in adolescents, employing structural equation modeling. Method. Tests were administered to 434 high school students. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 27 publications
3
28
1
2
Order By: Relevance
“…Thus, our findings confirm the results of Poon (2018), who found no significant relationship between Hot and Cool EF measures in a group of 12 to 17-year-old boys and girls. However, our results do not confirm the findings of Fino et al (2014), that impulsivity is a predictor of EF. With regard to the question why there is no influence of sports type and performance level, several explanatory approaches be worth considering.…”
Section: Discussion Of Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, our findings confirm the results of Poon (2018), who found no significant relationship between Hot and Cool EF measures in a group of 12 to 17-year-old boys and girls. However, our results do not confirm the findings of Fino et al (2014), that impulsivity is a predictor of EF. With regard to the question why there is no influence of sports type and performance level, several explanatory approaches be worth considering.…”
Section: Discussion Of Resultscontrasting
confidence: 99%
“…In this regard, Romer (2010) and Romer et al (2017) respectively subdivide impulsivity into the three forms sensation seeking, impatience and acting without thinking, the last two being related to low EF. Fino et al (2014) also confirm the interaction between impulsivity and EF by showing that impulsivity is a predictor of EF in college students. In particular, acting without thinking, also known as motor impulsivity (Romer et al, 2009), seems to be important in sports, as it means a weak ability to consider different alternatives in, e.g., complex game situations or to be "mindless" at a party the night before an important competition.…”
Section: Role Of Executive Functions In Elite Sportsupporting
confidence: 67%
“…In contrast, individuals who grew up in higher‐SES environments took fewer risks and displayed lower impulsivity and stronger preference for delayed rewards. Impulsivity (e.g., Fino et al ; Romer et al ), temporal discounting (e.g., Boyle et al ), and behavioral disinhibition (e.g., Barkley ) are all characteristics associated with low executive functioning.…”
Section: The Human Capital Catch‐22: Life Factors That Create Need Fomentioning
confidence: 99%
“…Self‐reporting impulsiveness has been found to be highly correlated with executive functions and inhibitory control capacity in adolescents and youth (Enticott, Ogloff & Bradshaw ; Fino et al . ). Furthermore, functional imaging studies have suggested that high impulsivity in IGD closely correlates with abnormalities in brain regions underlying executive control (Ding et al .…”
Section: Introductionmentioning
confidence: 97%